Inflammation and genes - Marklová, Eliška (Acta Medica, 2007)
Inflammation is a protective immune response to infection, trauma, or injury; however, only a subset of patients develops inflammation, suggesting other contributing factors involved, such as the environment and genes. Inflammationassociated genes involving those with pro- and anti-inflammatory effect should be properly balanced and regulated; the protein products of these genes ultimately determine the outcome of inflammation. Apart from gene mutations, gene polymorphisms related to some inflammatory markers also appear to correlate with the incidence and/or outcome of serious inflammatory events. Some genes recently recognized to be associated with inflammation are briefly reviewed. Modern genomic approaches, such as DNA micro-arrays and serial analysis of gene expression, allow for determining the extremely complex profile of inflammatory genes.
Keywords: Genetic Techniques; genetické techniky; exprese genu; Inflammation; Immune System Diseases; lidé; zánět; nemoci imunitního systému; financování vládou; Financing, Government; lékařská genetika; Genetics, Medical; Polymorphism, Genetic; Gene Expression; polymorfismus genetický; Humans